2011
DOI: 10.1002/hed.21667
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy with flutamide for presurgical volume reduction in juvenile nasopharyngeal angiofibroma

Abstract: Prepubertal and postpubertal patients differ in their response to flutamide. In postpubertal patients, 6 weeks preoperative use is safe and leads to partial tumor regression. Tumor regression from adjacent vital structures may facilitate surgical excision and limit morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…However, it is of particular interest in partial volume reduction. [14][15][16] None of the patients in this study had adjunctive therapy for tumour size reduction. Anaesthesiologists must be aware of these treatment modalities and their side-effects.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it is of particular interest in partial volume reduction. [14][15][16] None of the patients in this study had adjunctive therapy for tumour size reduction. Anaesthesiologists must be aware of these treatment modalities and their side-effects.…”
Section: Discussionmentioning
confidence: 94%
“…12,14 There have been conflicting recommendations in different studies with regard to flutamide, an androgen receptor blocker, which has been found to have unproven efficacy. However, it is of particular interest in partial volume reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Further, VEGF receptor expression was near universal and not associated with tumor stage, intraoperative blood loss or recurrence on follow-up. Anti-androgen treatment with flutamide has been demonstrated to bring about tumor regression in JA [11]. Tumor regression by medical therapies has been used in bringing about presurgical tumor shrinkage and so aiding and enabling less invasive surgical approaches.…”
Section: Discussionmentioning
confidence: 98%
“…Further, JA is an androgen sensitive tumor and various steroid receptors (androgen, estrogen, and progesterone receptors) are expressed on this tumor. Androgen blockage with flutamide (anti-androgen) has been used clinically to bring about presurgical tumor reduction and so aid surgical excision [11] and in vitro evaluation suggests that estrogen blockade with Tamoxifen may also inhibit tumor cell growth [12]. Though surgical excision is the mainstay of treatment, preoperative tumor shrinkage with neo-adjuvant drugs (either steroid receptor inhibitors or monoclonal antibodies against the growth factors) has the potential to significantly reduce surgical morbidity, and perhaps also to reduce intra-operative blood loss and tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Flutamide has been shown to reduce stage I and II tumor volume by 44 %, but has not shown any significant improvement over surgical resection alone of tumors of this stage. In the largest case series of 20 patients, it was noted that postpubertal male patients were most likely to respond compared to prepubertal; and in those that had a greater than 25 % tumor regression, the final surgical approach that was undertaken was more conservative than the approach planned at initial presentation [38]. The only reported side effect was that of breast tenderness.…”
Section: Flutamidementioning
confidence: 96%